The media and information environments ten years after 9/11 / Gary D. Rawnsley - Rawnsley, Gary D. (CMIWS and UiTM Press, 2011)
‘Cameras are now in places where cameras never used to be’ (Mark Lukasiewicz, NBC News Vice-President, 2007)2.‘almost by definition… a war waged on live television is a war in which political and public relations considerations become inextricably bound up with military tactics and strategy… how victory is won is almost important as victory itself’ (Washington Post, 24 March 2003).